Tumour necrosis factor blockade increases lymphangiogenesis in murine and human arthritic joints. Issue 11 (3rd January 2008) - Polzer, K; Baeten, D; Soleiman, A; Distler, J; Gerlag, D M; Tak, P P; Schett, G; Zwerina, J
Abstract : Objective: To investigate the presence and regulation of lymphatic vessels in inflamed joints of mice with experimental arthritis as well as patients with rheumatoid arthritis (RA) and spondyloarthritis (SpA). Methods: Lymphatic vessels and blood vessels were assessed in synovial tissue of human tumour necrosis factor transgenic (TNFtg) mice and synovial biopsies from patients with RA and SpA by immunohistochemistry for podoplanin and CD31, respectively. Assessments were performed before and after TNF blockade in all biopsies. Results: Lymphatic vessels were abundantly present in the synovial tissue of hTNFtg mice as well as patients with RA and SpA. The number of lymphatic vessels was positively related to the severity of synovial inflammation. Treatment with infliximab led to an increase in the formation of lymphatic vessels in murine and human inflammatory tissue. Conclusions: This study shows that TNF blockade promotes the proliferation of lymphatic vessels in the inflamed synovium of RA and SpA. This finding leads to the assumption that promotion of lymphangiogenesis may play an important part in efflux of cells and fluid out of the inflamed tissue.